Perlindungan Hukum Terhadap Konsumen Yang Dirugikan Atas Perbuatan Kartel Produsen Kendaraan Bermotor - Chelsea Angelia Hartono; Lanny Kusumawati; Irta Windra Syahrial (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This thesis raises a case regarding the actions and implementation of a cartel agreement between the President Director of PT X and the President Director of PT Y with the object of a 110 cc & 125 CC automatic scooter that does not meet the statutory provisions, namely article 1320 number (4), 1338 paragraph (3) and 1365 of the Criminal Code in conjunction with Article 5 paragraph (1), Article 11, and 47 of Law No. 5 of 1999 in conjunction with Article 4 and Article 45 paragraph (1) of Law No. 8 of 1999, which resulted in unlawful acts. The non-compliance with the statutory provisions was because the automatic scooter motorcycle was motivated by the existence of a cartel agreement between the President Director of PT X and the President Director of PT Y in violation of Article 5 paragraph (1). So that the price fixing agreement made has violated the legal requirements of an agreement, namely